USING UNMALTED BARLEY FOR BREWING - Loiko, Sergii; Romanova, Zoriana (Proceedings of National Aviation University, 2018)
Purpose: The main raw material for beer production is malt. There is a tendency to use other grain crops in the production of beer. The using of unmalted materials gives opportunity for brewers and technologist for cost saving. But replacing of malt makes affects the quality of wort and beer. The purpose of the researches was to compare quality parameters of 100% malt beers and beer with part of malt replaced by unmalted barley. Methods: To solve the given problem the methods of the high-performance liquid chromatography, analysis and empirical methods are used. Results: Using a big amount of unmalted grits together with external enzymes gives brewers opportunity to receive product in the same composition and quality like high-quality product using only malt. Conclusions: For brewing with a very small amount of malt, barley is a very good choice for replacing part of it as it has some characteristics of malt. It is possible, economically profitable and technically reasoned to replace half of the malt in the grind. But it becomes necessary to use exogenous enzymes.